Analysis of Nutritional Intake Determinants and Anemia Incidence in Adolescent Girls in Senior High Schools in Bone Bolango Regency - Amanda Iin Melisa P.H. Harun; Sunarto Kadir; Vivien Novarina A. Kasim (Jambura Medical and Health Science Journal, 2026)
Introduction: Anemia is a pathological state defined by a reduction in red blood cell mass, evidenced by decreased hemoglobin concentrations (11 g/dL), hematocrit values, and erythrocyte counts. Preliminary data indicate that out of 3,073 adolescents screened for hemoglobin levels in Bone Bolango Regency, 225 were identified as anemic. This study aims to investigate the factors contributing to the prevalence of anemia among female high school students in this regency.Method: This study was carried out in three schools in Tapa District, using a quantitative research design. The sample comprised 225 adolescent girls of reproductive age. Logistic regression analysis was used to examine the relationships between anemia incidence and several independent variables, including iron tablet consumption, iron intake, protein intake, vitamin C intake, vitamin B12 intake, zinc intake, meal frequency, and dietary diversity.Results: The findings indicated that among the adolescent female population in Bone Bolango Regency, 77 individuals were anemic, whereas the remaining 148 presented with normal hemoglobin levels. Bivariate analysis revealed that iron intake was the only variable significantly associated with the occurrence of anemia, with no other factors demonstrating a statistically significant relationship.Conclusion: This study demonstrates that iron intake is the primary determinant significantly associated with anemia among adolescent girls, showing a stronger influence than other nutritional factors and variables examined in the study.Keywords: Adolescent girls, anemia, dietary diversity, iron intake, meal frequency